2020
DOI: 10.1136/ijgc-2020-001585
|View full text |Cite
|
Sign up to set email alerts
|

Change in practice in gynecologic oncology during the COVID-19 pandemic: a social media survey

Abstract: ObjectiveCOVID-19 has affected gynecologic cancer management. The goal of this survey was to evaluate changes that occurred in gynecologic oncology practice during the COVID-19 pandemic.MethodsA anonymous survey consisting of 33 questions (https://sites.google.com/view/gyncacovidfmartinelli) regarding interaction between gynecologic cancers and COVID-19 was distributed online via social media from April 9 to April 30, 2020. Basic descriptive statistics were applied. Analytics of survey-diffusion and generated-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
48
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(55 citation statements)
references
References 16 publications
6
48
1
Order By: Relevance
“…The study by F. MARTINELLI, A. GARBI. [7] , carried out on social networks in 49 countries and questioning 187 consultants on the changes in management of gynecological cancers, found similar results to our study. In their study, a change in treatment strategy with respect to chemotherapy was found in 30 to 40% of cases, a halt in laparoscopic surgery in 30% of cases and an increase in treatment with radiotherapy in 24% of cases.…”
Section: Discussionsupporting
confidence: 88%
“…The study by F. MARTINELLI, A. GARBI. [7] , carried out on social networks in 49 countries and questioning 187 consultants on the changes in management of gynecological cancers, found similar results to our study. In their study, a change in treatment strategy with respect to chemotherapy was found in 30 to 40% of cases, a halt in laparoscopic surgery in 30% of cases and an increase in treatment with radiotherapy in 24% of cases.…”
Section: Discussionsupporting
confidence: 88%
“…Surveys of physicians across varied specialties have unanimously demonstrated marked disruptions in clinical practice due to the pandemic. 7–10 Interestingly, these disruptions encompass not only elective procedural volumes but also reductions in urgent and emergent procedures. Studies have reported decreased admissions for ischemic stroke, 11 a substantial reduction in mechanical thrombectomy volumes, 12 and a sharp decline in the number of stroke imaging evaluations at the height of the pandemic.…”
Section: Introductionmentioning
confidence: 99%
“…Surveys designed to address highpriority issues in other medical specialties have unanimously demonstrated marked disruptions in clinical practice. [27][28][29][30] Although the present study did not specifically address the effects of COVID-19 on neurovascular research, a concomitant study has also revealed widespread disruptions in aneurysm and stroke clinical trials due to missed enrollments and protocol deviations from missed clinical or imaging follow-up 31 These broad vantage points are particularly important given the widespread fears about resurgent infection, 32 33 with the persistence of the virus in communities across the US. This data helps inform current responses, but also future ones in the event of subsequent pandemics.…”
Section: Discussionmentioning
confidence: 99%